Biophysical studies of motions and interactions of membrane proteins - Winter, Peter William, author; Barisas, B. George, advisor; Roess, Deborah A., advisor; Crans, Debbie C., committee member; Bamburg, James R., committee member (Colorado State University. Libraries, 2011)
We have utilized a variety of biophysical techniques to quantitatively examine the motions and interactions of transmembrane proteins on living cells at the single-molecule level. These include both widefield and confocal optical microscopic methods such as single particle tracking, Förster resonance energy transfer and ratiometric imaging of phase-sensitive probes of lipid order, together with spectroscopic fluctuation methods such as fluorescence correlation spectroscopy and photon counting histogram analysis. Our studies indicate that; 1. Luteinizing hormone receptors on CHO cells and KGN human granulosa cells exhibit restricted lateral diffusion and increased self-association after exposure to human chorianic gonadotropin; 2. In addition to insulin receptor and IGF1 receptor homodimers, rat basophilic leukemia 2H3 cells express significant levels of insulin receptor-IGF1 receptor heterodimers; 3. Clustering of insulin receptors after exposure to insulin on rat basophilic leukemia 2H3 cells is affected by disruption of actin-filaments but not by extraction of membrane cholesterol; 4. Chromium Picolinate and Bis(maltolato)oxovandium(IV) both restrict the lateral diffusion of insulin receptors on rat basophilic leukemia cells and; 5. Individual FcE receptors on rat basophilic leukemia cells exhibit orientation fluctuations on millisecond timescales.